Expert consensus statement on therapeutic drug monitoring and individualization of linezolid - Lin, Bin; Hu, Yangmin; Xu, Ping; Xu, Tao; Chen, Chunyan; He, Le; Zhou, Mi; Chen, Zhangzhang; Zhang, Chunhong; Yu, Xuben; Fang, Luo; Zhu, Junfeng; et al. (Frontiers in Public Health, 2022)
Linezolid is an oxazolidinone antibacterial drug, and its therapeutic drug monitoring and individualized treatment have been challenged since its approval. With the in-depth clinical research of linezolid, we have changed our attitude toward its therapeutic drug monitoring and our view of individualized treatment. On the basis of summarizing the existing clinical studies, and based on the practical experience of each expert in their respective professional fields, we have formed this expert consensus. Our team of specialists is a multidisciplinary team that includes pharmacotherapists, clinical pharmacology specialists, critical care medicine specialists, respiratory specialists, infectious disease specialists, emergency medicine specialists and more. We are committed to the safe and effective use of linezolid in patients in need, and the promotion of its therapeutic drug monitoring.